THE ROLE OF BANK SIZE IN MODERATING THE IMPACT OF CREDIT PORTFOLIO DIVERSIFICATION ON BANK PROFITABILITY IN ASEAN - Ginaya Mughni Utami Hasibuan; Syarief Fauzie (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the impact of credit portfolio diversification on bank profitability, with a specific focus on the moderating role of bank size in ASEAN commercial banks. Using a panel dataset comprising 56 banks across six ASEAN countries from 2017 to 2023, the research applies a random effects panel regression model to analyze the effect of credit concentration, measured by the Herfindahl-Hirschman Index (HHI), on Return on Assets (ROA). The results reveal a significant negative relationship between HHI and ROA, indicating that higher diversification enhances profitability. Additionally, the interaction between HHI and bank size (measured by the logarithm of total assets) is negative and significant, suggesting that the positive effect of diversification weakens as bank size increases. These findings are robust across multiple model specifications and control variables, including capital adequacy, credit risk, liquidity, inflation, GDP growth, and state ownership. The study highlights the nuanced dynamics between diversification and institutional scale and provides implications for both banking strategy and regulatory policy. It recommends size-sensitive diversification approaches and capital management strategies to maximize performance outcomes in the ASEAN banking sector.